Preserving fertility in young adolescents with cancer - an oncofertility perspective - Kwieciński, Jakub; Leśniak, Marek; Błaszczyk, Agnieszka; Fussek-Styga, Urszula; Trojan, Sara; Miszuda, Sławomir; Basiaga, Bartosz; Bednarz, Krzysztof; Szwedkowicz, Agata; Heluszka, Jakub (Quality in Sport, 2023)
Oncofertility is an emerging field at the intersection of oncology and reproductive medicine that aims to address the fertility-related consequences of cancer treatment. Advances in cancer diagnosis and treatment have led to significant improvements in survival rates, but many cancer treatments can cause infertility or premature ovarian failure, which can have a profound impact on the quality of life and overall well-being of cancer survivors. Oncofertility seeks to provide patients with the opportunity to preserve their reproductive potential before undergoing cancer treatment, thus ensuring that they have options for starting a family after treatment. This field encompasses a range of approaches, including fertility preservation techniques. While oncofertility is still a relatively new field, it has already made significant strides in improving the quality of life for cancer survivors. However, there are still many challenges that must be addressed, including access to oncofertility services and the development of new and more effective techniques. This paper will explore the current state of oncofertility research and highlight some of the key challenges and opportunities in this important field.